2017
DOI: 10.18203/2320-6012.ijrms20171871
|View full text |Cite
|
Sign up to set email alerts
|

To study the thyroid profile in menstrual disorder at tertiary care hospital in northern western Rajasthan, India

Abstract: Background: Abnormal uterine bleeding is a common but complicated clinical presentation. It is one of the most frequently encountered conditions in gynaecology and is defined as abnormal bleeding from the uterus. Methods: Present prospective study was conducted on 100 patients who presented with abnormal uterine bleeding at Sardar Patel Medical College, Bikaner, Rajasthan, India. Results: Among 100 women, 39 had hypothyroidism, 8 patients had hyperthyroidism rest 53 were euthyroid. Out of 39 hypothyroid patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 2 publications
2
7
0
Order By: Relevance
“…9 Jinger SK et al found 47% patients having thyroid dysfunction in their study and 53% euthyroid. 6 The main thyroid dysfunction noted was hypothyroidism including subclinical (17%) and overt hypothyroidism (15%) in our study. Similarly, in the study by Marimuthu K et al 15.6% were hypothyroid, 3.2% had subclinical hypothyroidism and 7.2% were hyperthyroid.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…9 Jinger SK et al found 47% patients having thyroid dysfunction in their study and 53% euthyroid. 6 The main thyroid dysfunction noted was hypothyroidism including subclinical (17%) and overt hypothyroidism (15%) in our study. Similarly, in the study by Marimuthu K et al 15.6% were hypothyroid, 3.2% had subclinical hypothyroidism and 7.2% were hyperthyroid.…”
Section: Discussionmentioning
confidence: 46%
“…5 Surendra Kumar Jinger et al in their study of 100 women with AUB had 49% in 20-30 yr age group. 6 Pilli et al reported that AUB is seen in 87% multipara, 7% primipara and 6% nulliparous. 5 In present study also majority of patients were multiparous (54%).…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Marimuthu K et al, out of 250 cases of AUB, 68 (27.2%) cases had thyroid dysfunction [10]. Surendra Kumar Jinger et alfound 47% patients having thyroid dysfunction in their study and 53% euthyroid [7]. The main thyroid dysfunction noted was hypothyroidism including subclinical (17%) and overt hypothyroidism (15%) in our study.…”
Section: Discussionsupporting
confidence: 52%
“…Pilli et alhad 58% cases in age group of 21-30 years [6]. Surendra Kumar Jinger et al in their study of 100 women with AUB had 49% in 20-30 yr age group [7]. Pilli et alreported that AUB is seen in 87% multipara, 7% primipara and 6% nulliparous [6].…”
Section: Discussionmentioning
confidence: 99%
“…5 Jinger SK et al, in their study of 100 women with AUB had 49% in 20-30 years age group. 6 Pilli et al, reported that AUB is seen in 87% multipara, 7% primipara and 6% nulliparous. 5 In present study also majority of patients were Para 2 (20%).…”
Section: Discussionmentioning
confidence: 99%